Intersepsi Hujan pada Berbagai Umur Tanaman Kelapa - NOLI L. BARRI (Pusat Penelitian dan Pengembangan Perkebunan, 2010)
The Rainfall Interception of Different Age of CoconutDistribution of the amount of water available in coconut plantation determined not only by supply from outside in the form of rain or irrigation, but also is determined by planting distance, planting system and age of coconut. Some researches indicates a significant correlation between the rainfall intensity and the agronomic properties of plants with the amount of trough fall, net or effective rainfall and canopy interception. Therefore, the distribution of rain in coconut palms in different ages need to be studied. The main objective of this research is to know the difference of trough fall, effective rainfall and rainfall interception in of coconut palms in different ages. The research was done observation methode the coconut palms were selected purposively based on the coconut ages (5, 20 and 50 years old). For measuring the rainfall distribution at each coconut plantation used from coconut palms.The results showed that the average trough fall of 5, 20, and 50 years old coconut palms was 53.67, 31.14, and 39.21 percent of average rainfall, respectively. Effective rainfall or net rainfall that reached the area in coconut plantations did not differ with trough fall. The average rainfall interception of canopy 5, 20, and 50 years old were coconut plantation was are respectively 46.33, 68.82, and 23.51 percent of rainfall. The relationship during rainfall intensity and trough fall and effective rainfall is positive linear. Its meaning that the higher rainfall intensity will followed by the greater of trough fall and the effective rainfall.In the otherside, the In the other side the relations between rainfall intensity and canopy interception is logarithmic. At means that each canopy in different age of coconut have a certain capacity to hold rain water. Capacity of coconut canopy 5, 20, and 50 years old to hold water of rain were 1.171 , 2.219, and 0.896 mm respectively.